1985
DOI: 10.1128/jb.161.2.681-686.1985
|View full text |Cite
|
Sign up to set email alerts
|

Proton circulation in Vibrio costicola

Abstract: The importance of proton movements was assessed in the moderate halophile Vibrio costicola. When anaerobic cells in acidic buffer (pH 6.5) were given an 02 pulse, protons were extruded regardless of the presence of Na+. At pH 8.5, however, V. costicola produced an acidic response to an 02 pulse in the absence of Na+ and an alkaline response when Na+ was present. An Na+/H+ antiport activity was confirmed at pH 8.5. All of these effects were prevented by protonophores or butanol treatment. Growth in complex medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Na ϩ /H ϩ antiporters have been characterized from moderately halophilic bacteria that mainly use organic solutes, such as Salinivibrio costicola (38,39). These antiporters play a key role in keeping the intracellular Na ϩ concentrations low.…”
Section: Ion Pumping In Microorganisms That Accumulate Organic Solutesmentioning
confidence: 99%
“…Na ϩ /H ϩ antiporters have been characterized from moderately halophilic bacteria that mainly use organic solutes, such as Salinivibrio costicola (38,39). These antiporters play a key role in keeping the intracellular Na ϩ concentrations low.…”
Section: Ion Pumping In Microorganisms That Accumulate Organic Solutesmentioning
confidence: 99%
“…It is generally accepted that Na ϩ /H ϩ antiport activity is an important mechanism for maintaining low intracellular sodium concentrations. The Na ϩ /H ϩ antiporter activity of S. costicola has been relatively well studied (105,106,332). However, there is still considerably controversy about the occurrence and relative importance of primary Na ϩ pumps in different representatives of the very heterogeneous group of moderate halophiles.…”
Section: Ion Pumps In the Cell Membranesmentioning
confidence: 99%
“…All these effects are abolished by protonophores. At pH 8.5, growth is prevented by CCCP (at the rather high concentration of 50 M [see below]) and by TCS (106). During growth on lactate as the energy source, Na ϩ translocation in S. costicola was inhibited by CCCP but little affected by valinomycin.…”
Section: Ion Pumps In the Cell Membranesmentioning
confidence: 99%
“…These workers concluded that a respiration-dependent primary electrogenic Na + pump functions in this organism at alkaline pH which would be responsible for generating both the uncoupler insensitive membrane potential and the Na + gradient. Hamaide et al, with Vibrio costicola [20], and Krulwich with the alkalophilic bacteria [21], however, have concluded that in these organisms their results at alkaline pH can be explained by a primary pumping of protons followed by a secondary extrusion of Na + by the Na+/proton antiporter if the appropriate stoichoimetry of proton and Na + movement is maintained.…”
Section: Energetics Of Membrane Trans-portmentioning
confidence: 99%